Kinematic Factors of Sitting Posture for Musculoskeletal Pain in University Staff - , Dhenyffer Bruna Almeida Perez, Bruno Sergio Portela (Archives of Current Research International, 2024)
Aims: The objective of the present study was to verify the relationship between musculoskeletal pain and kinematic factors of sitting posture in university staff at the University of Middle-West –UNICENTRO. Methodology: The sample studied was 24 university agents from a total of 40 employees. Anthropometric data were collected by record and to assess the prevalence of pain, a standardized questionnaire was used. The employee positioning variables were: popliteal height, elbow-to-seat height, table height and thigh height. The arrangement of the workstation was also evaluated, checking the position of the computer and/or other equipment for daily use. Results: It was found that 54.16% of the agents had some type of pain in the spine. The recommended chair seat for men would be a height of 44.3 cm and was found to be 50.2 cm, while for women the recommended height is 40.9 cm and was found to be 45.1 cm. Conclusion: According to the results obtained, the height of the table was higher than recommended, which could perhaps justify the complaint of pain reported by university agents.